Study the Level of Zinc, Copper and Magnesium on Iraqi Diabetic Patients - Hiba Abid Al-Hussein Hassan (Journal of Global Pharma Technology, 2018)
This studyamidto measure and compare the levels of serum 0zinc, copper and magnesium0 ions in healthy individuals and diabetic0 patients. Its involved 80 patients, their age range from (20-80) years.  The study divided into three groups: T1DM (40) patients, T2DM (40) patients and (40) healthy subject as control groups .Analysis of zinc ,copper and magnesiumions was done in serum by using auto analyzer  spectroscopy,whileserum glucosewas determined by enzymatic methods using linear chemicals kit. This project done during period from (November 2015 to Jun. 2016) at teaching laboratories and medical city / Baghdad. The study showed0 a definite lowering of serum0 magnesium (p<0.01) and serum zinc0 levels (p<0.01) while increasing0 of serum copper (p<0.01) in diabetic group compared with the healthy control groups.Keywords: Diabetes Mellitus, copper, Zinc, Magnesium.